Implications of Narcotics Crime Regulation in the National Criminal Code Against Narcotics Abusers - Diani, Silvana; Puluhulawa, Fenty U.; Ismail, Dian Ekawaty; Handayani, Distya Putri (JURNAL LEGALITAS, 2024)
This article aims to determine and analyze the application of the law to drug abusers and addicts based on Law Number 5 of 2009 on Narcotics and Law Number 1 of 2023 on the Criminal Code. Furthermore, to know, analyze, and construct drug crime arrangements that ensure legal protection for drug abusers and addicts. This article is normative research with a statutory approach, a case approach, a historical approach, and a conceptual approach. The results show that first, the application of the law against drug abusers and addicts has many problems, especially in the implementation of the law on narcotics. This problem has implications for regulatory bias in some articles, such as in Articles 4 and 54, which cause differences in subjects who are obliged to undergo medical rehabilitation and social rehabilitation. Furthermore, there is a tendency to use Article 111 or Article 112 charged with Article 127 (if an alternative charge) or without Article 127 (if a single charge) against drug abusers and drug users. This trend illustrates that the approach used is criminal, even if it is towards drug users, not drug dealers. Furthermore, the regulation of drug crimes in the New Criminal Code basically does not eliminate these problems because the provisions maintained through the New Criminal Code are only copies of repealed articles and no longer apply to the law on narcotics. Second, criminal regulation that ensures legal protection for drug abusers and addicts can be realized by revising the law on narcotics, which focuses on subject consistency in Article 54, Article 55, and Article 103, changing the elements of Article 127 paragraph (3) and abolishing the Explanation to Article 54.